Congenital myasthenic syndromes in adult neurology clinic: A long road to diagnosis and therapy. (6th November 2018) - Kao, Justin C.; Milone, Margherita; Selcen, Duygu; Shen, Xin-Ming; Engel, Andrew G.; Liewluck, Teerin
Abstract : Objective: To investigate the diagnostic challenges of congenital myasthenic syndromes (CMS) in adult neuromuscular practice. Methods: We searched the Mayo Clinic database for patients with CMS diagnosed in adulthood in the neuromuscular clinic between 2000 and 2016. Clinical, laboratory, and electrodiagnostic data were reviewed. Results: We identified 34 patients with CMS, 30 of whom had a molecular diagnosis (14 DOK7, 6 RAPSN, 2 LRP4, 2 COLQ, 2 slow-channel syndrome, 1 primary acetylcholine receptor deficiency, 1 AGRN, 1 GFPT1, and 1 SCN4A ). Ophthalmoparesis was often mild and present in 13 patients. Predominant limb-girdle weakness occurred in 19 patients. Two patients had only ptosis. Age at onset ranged from birth to 39 years (median 5 years). The median time from onset to diagnosis was 26 years (range 4–56 years). Thirteen patients had affected family members. Fatigable weakness was present when examined. Creatine kinase was elevated in 4 of 23 patients (range 1.2–4.2 times the upper limit of normal). Repetitive nerve stimulation revealed a decrement in 30 patients. Thirty-two patients were previously misdiagnosed with seronegative myasthenia gravis (n = 16), muscle diseases (n = 15), weakness of undetermined cause (n = 8), and others (n = 4). Fifteen patients received immunotherapy or thymectomy without benefits. Fourteen of the 25 patients receiving pyridostigmine did not improve or worsen. Conclusion: Misdiagnosis occurred in 94% of the adult patients with CMS and causes a median diagnostic delay of nearly 3 decades from symptom onset. Seronegative myasthenia gravis and muscle diseases were the 2 most common misdiagnoses, which led to treatment delay and unnecessary exposure to immunotherapy, thymectomy, or muscle biopsy.